(untitled) (AYUSHDHARA, 2020)
Human is evolved and nourished by food so food has been given the prime importance since Vedic period, but if our food itself is polluted then how the development of health hazards can be prevented or checked. The contamination of food is a major concern especially for developing countries like India. Today, society are very careful about the selection of food but unfortunately attention has not been given about selection of cookware and the impact of these cooking utensils on health. Number of good looking cookware sets are made by very dangerous material and coated by toxic chemicals to. Most commonly used cookware sets are Aluminum, Plastic and Non-stick cookware. During cooking process these cookware sets releases many hazardous substances like Teflon, BPA, Aluminum etc., which contaminates food and ultimately reaches to the body and linked as a causative factor for many diseases like Cancer, Alzheimer’s disease etc. According to FDA materials that are used to make utensils should not allow to migrate into food. Though, traditionally Earthen pots, Cast- iron, glass, bamboo and copper, stone cookware sets were in use. Those were added therapeutic value in the cooked food. Thus, attention must be needed to choose the correct utensils for cooking which should be safe and beneficial for health. In Ayurveda during the description of eight dietary principles, importance of Vasana (utensils) is mentioned under the description of Karana (processing techniques of food items). Ayurveda believes that container helps in transformation of qualities of food items. Different kinds of utensils had been shown both positive and negative effect on body. Hence, this article makes an attempt to gathered data and compiled to find the health impacts of newly evolved as well as traditional cookware options in society.